Bacterial Exopolysaccharides as Reducing and/or Stabilizing Agents during Synthesis of Metal Nanoparticles with Biomedical Applications. (3rd September 2018) - Escárcega-González, Carlos Enrique; Garza-Cervantes, Javier A.; Vázquez-Rodríguez, Augusto; Morones-Ramírez, José Rubén
Abstract : Bacterial exopolysaccharides (EPSs) are biomolecules secreted in the extracellular space and have diverse biological functionalities, such as environmental protection, surface adherence, and cellular interactions. EPSs have been found to be biocompatible and eco-friendly, therefore making them suitable for applications in many areas of study and various industrial products. Recently, synthesis and stabilization of metal nanoparticles have been of interest because their usefulness for many biomedical applications, such as antimicrobials, anticancer drugs, antioxidants, drug delivery systems, chemical sensors, contrast agents, and as catalysts. In this context, bacterial EPSs have been explored as agents to aid in a greener production of a myriad of metal nanoparticles, since they have the ability to reduce metal ions to form nanoparticles and stabilize them acting as capping agents. In addition, by incorporating EPS to the metal nanoparticles, the EPS confers them biocompatibility. Thus, the present review describes the main bacterial EPS utilized in the synthesis and stabilization of metal nanoparticles, the mechanisms involved in this process, and the different applications of these nanoparticles, emphasizing in their biomedical applications.